Analysis of the Impact of Economic Regulation on Business Stability in the Context of Modern Business Law - Dony Sipayung, Parlin; Gultom, Sarles; Elpina; Lodewijk Purba, Van (UNES Law Review, 2024)
The purpose of this research is to examine the implications of business law on the practice of business ethics in Indonesia. To achieve this, a library-based research methodology was employed, with relevant data being gathered from various sources of literature pertinent to the research topic. The results demonstrate that there is a significant influence exerted by business law upon business ethical practice in Indonesia. In essence, business law establishes the legal rights and obligations that arise from business agreements and business ties. Moreover, a variety of additional factors influence the implementation of business law in ethical and responsible business practices, including national development, business ethics, internal and external factors, and legal awareness. To address this issue, a number of potential solutions and recommendations have been put forth. These include the strengthening of regulations, more effective law enforcement, the provision of education and awareness, collaboration between the government and business leaders, greater transparency and accountability, and the creation of an independent oversight body. It is anticipated that the implementation of these solutions will create a fair, transparent and ethical business environment, which will positively influence economic development and the general welfare of the Indonesian population.